Testing the Psychometric Properties of the Interpersonal Reactivity Index (Iri) in Chile: Empathy in a Different Cultural Context - Fernandez-Tapia, A (2011)
The psychometric properties of Davis (1980) Interpersonal Reactivity Index (IRI) in Chile were assessed. The IRI was applied to a sample of 435 college students. Appropriate internal consistencies and test-retest stability resulted. The instrument s validity was evidenced by the interrelations among the scales, in addition to its correlations in the predicted direction to other related psychological constructs, and sex differences emerged in three of its dimensions. A confirmatory factor analysis corroborated the theoretical structure of the IRI in Chile, and the suitability of both the four-factor model and a second order factor that integrates three of the dimensions. The implications and comparison of the results with other adaptations of the IRI are discussed. © 2011 Hogrefe Publishing.